Prevalence of Brucellosis in Humans and Cattle in Selected Areas of Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Brucellosis is a recognized public health problem and one of the major causes of morbidity both in humans and animals. It causes abortion and infertility in women and livestock as well.Objective: The research was carried out to know the prevalence and to identify the risk factors of brucellosis in humans and cattle in study areas in Bangladesh.Materials and Methods: The study areas were all Upazilas of Mymensingh, Jamalpur, Rangpur, Kurigram, Bagerhat and Gaibandha district and the Government owned Central Cattle Breeding and Dairy Farm (CCBDF) in Savar, Dhaka for cattle and human samples were collected from Mymensingh Medical College Hospital, Mymensingh, Bangladesh. A total livestock samples collected were 1043 and human samples were 460. Besides doing all the tests in Bangladesh Agricultural University, Mymensingh Medical College and Hospital laboratory Bangladesh, it was done also in Office International des Epizooties (OIE) world reference Laboratory in Jena, Germany.Results: Out of 1043, 28 milk samples (2.68 %) and 23 serum samples (2.21 %) were positive by MRT and RBT respectively. The highest prevalence was 3.05% in the Holstein Friesian cross using MRT, while 2.49% in the Holstein Friesian cows using RBT. Age-wise prevalence of brucellosis by MRT and RBT were 2.06% and 1.23% respectively in 1-4 years age group. On the other hand prevalence of brucellosis based on MRT and RBT were significantly higher (2.88% and 2.50%) in > 5 years age group (p≤0.01) than those of other age groups. Based on parity, significantly higher prevalence 3.07% and 2.58% of MRT and RBT were obtained respectively in parity 3-5 in comparison to other parity group (p≤0.01).In case of human brucellosis 460 blood samples were tested with RBT, SAT, CFT, iELISA, conventional PCR and real time PCR but were negative in all tests. In case of livestock and human brucellosis bacteria were cultured in OIE Reference Laboratory, Federal Research Institute for Animal Health, but bacteria were not isolated.Conclusion: The prevalence of brucellosis is asserted in human and cattle in this study although MRT is 1st-line screening tests for brucellosis. Whereas no human samples were found positive for brucellosis in this study.Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 33-36